The Effectiveness of Media Disc Triage Assessment on Clinical Reasoning Skills of Australasian Triage Scale (ATS) in Nursing Students - Nikma Alfi Rosida; Anissa Cindy Nurul Afni; Muhamad Nur Rahmad; Elok Faradisa; Sigit Yulianto (Indonesian Journal of Global Health Research, 2025)
Australasian Triage Scale (ATS) is a tool used by emergency department nurses to assess a patient's health status and prioritise services based on the severity of the patient's condition. Clinical Reasoning skills are cognitive processes in the form of theoretical applications and clinical abilities of a nurse in evaluating, diagnosing, and providing nursing care for patients based on information and condition. Objective: This study aims to evaluate the effectiveness of using learning tools by using media Disc Triage Assessment to improve clinical reasoning skills using ATS triage. Method: The research method used was quasi-experimental without control group design. A total of 193 nursing diploma students who passed the Emergency Nursing course were selected using purposive sampling. Therefore, the sample is 35 students. Data analysis was performed using Wilcoxon test. Result: The results were significant improvements across five domains of Nurses Clinical Reasoning Skills (NCRS): Assessment, Diagnosis, Intervention, Implementation, and Evaluation, all with p-values < 0.05. Conclusions: This has a significant positive effect on improving students' clinical reasoning skills in determining triage ATS. This shows can be effective in improving the ability of students to determine triage levels and make informed clinical decisions.